2020
DOI: 10.2147/cmar.s245674
|View full text |Cite
|
Sign up to set email alerts
|

<p>microRNA-582 Potentiates Liver and Lung Metastasis of Gastric Carcinoma Cells Through the FOXO3-Mediated PI3K/Akt/Snail Pathway</p>

Abstract: Background: The dysregulation of microRNA (miRNAs) is broadly participated in cancer progression, resulting in sustained cell proliferation by directly targeting various targets. This study investigated the expression of miR-582 in GC and its association with liver metastasis. Methods: Firstly, differentially expressed miRNAs in gastric cancer (GC) tissues were predicted by microarray. Then, the relationship between miR-582 and clinical characteristics of GC patients was analyzed. By silencing of miR-582 in GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The PI3K/AKT signaling pathway also participated in liver metastasis of various malignant tumors. Indeed, microRNA-582 can promote gastric cancer liver metastasis via the PI3K/AKT/Snail pathway mediated by FOXO-3 ( Xie et al, 2020 ). The c-Met/PI3K/AKT/mTOR axis can activate the liver metastasis-specific cholesterol metabolism pathway in colorectal cancer, providing conditions for tumor cell colonization and growth in the liver ( Zhang et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway also participated in liver metastasis of various malignant tumors. Indeed, microRNA-582 can promote gastric cancer liver metastasis via the PI3K/AKT/Snail pathway mediated by FOXO-3 ( Xie et al, 2020 ). The c-Met/PI3K/AKT/mTOR axis can activate the liver metastasis-specific cholesterol metabolism pathway in colorectal cancer, providing conditions for tumor cell colonization and growth in the liver ( Zhang et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…They can inhibit or degrade their target mRNAs by binding to the 3′non-coding region of their target gene mRNA ( 18 , 19 ). It has been reported that miRNAs are involved in a series of important processes, such as tumor proliferation, invasion and migration ( 40 , 41 ). Increasing evidence suggest that lncRNAs and miRNAs can interact to cross-regulate the biological processes of tumor cells ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…GATA6-AS1 expression has been reported to be downregulated in gastric cancer, where it decreases frizzled class receptor 4 (FZD4) expression by recruiting zeste homolog 2 and inducing trimethylation at lysine 27 of histone H3 of the FZD4 promoter region, inhibiting therefore the Wnt/β-catenin signaling pathway and preventing epithelial-mesenchymal transition ( 7 ). Furthermore, downregulated expression of GATA6-AS1 activates the PI3K/AKT/Snail signaling pathway via regulation of miR-582/FOXO3 axis and subsequently promote the proliferation and metastasis of gastric cancer cells ( 23 ). The present study demonstrated that GATA6-AS1 expression was decreased in OC and that GATA6-AS1 significantly inhibited the proliferation and migratory and invasive abilities of OC cells, confirming that GATA6-AS1 may be a tumor-suppressive lncRNA in OC.…”
Section: Discussionmentioning
confidence: 99%